2009
DOI: 10.1080/01443610902862712
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception: Patterns of use in community sexual health clinics

Abstract: The reported uptake of the intrauterine device (IUD) as emergency contraception is very low despite its superior efficacy when compared with levonorgestrel emergency contraception. A prospective study was conducted to investigate the methods of emergency contraception offered to and accepted by women attending South Staffordshire Sexual Health Clinics. A total of 240 women attended the clinic for emergency contraception during the 2-month study period. The IUD as a method of emergency contraception was not off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, only one had been informed about the availability and greater reliability of the IUD as an alternative option to ECPs during previous consultations. Other studies 16,17 also found that the IUD is not offered to the majority of women attending for EC, in particular nulliparous women. In our study 25/26 women were offered EC-IUDs during this episode of care; one woman was either not offered, or did not remember having been offered the EC-IUD.…”
Section: Discussionmentioning
confidence: 93%
“…However, only one had been informed about the availability and greater reliability of the IUD as an alternative option to ECPs during previous consultations. Other studies 16,17 also found that the IUD is not offered to the majority of women attending for EC, in particular nulliparous women. In our study 25/26 women were offered EC-IUDs during this episode of care; one woman was either not offered, or did not remember having been offered the EC-IUD.…”
Section: Discussionmentioning
confidence: 93%
“…However, the copper IUD is used in only around 3% of patients presenting for EC. Its limited uptake may partly be due to the fact that the copper coil is offered as an option for EC to only a minority of women (Moss et al , 2009). Potential limitations that limit its use (Rickards et al , 2004) include:…”
Section: Providing An Overview Of Contraceptive Methodsmentioning
confidence: 99%
“…However, knowledge of the Cu-IUD for EC is limited among women and health care providers [53][54][55] and even experienced family planning providers rarely offer it as an option. 55,56 Barriers to its use may include lack of provider availability for urgent IUD insertion and the immediate cost of the IUD. Women for whom EC pills are likely to be less effective should be encouraged to consider a Cu-IUD (women with BMI ≥ 30, women delayed in presentation, and those presenting one day prior to, on the day of, or after presumed ovulation for hormonal EC).…”
Section: Providing Emergency Contraceptionmentioning
confidence: 99%